The Influence of Knowledge Management and Learning Organization on Competitive Advantage in Startups in Malang City with Organizational Creativity as a Mediating Variable (A Study on Startup Companies at Stasion Malang) - Enaldi Enaldi; Hamidah Nayati Utami; Tri Wulida Afrianty (Universitas Muhammadiyah Ponorogo, 2025)
This study explores the impact of learning organization and knowledge management on competitive advantage, with organizational creativity as a mediating variable, within Malangâ€™s startup ecosystem. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 104 startups. Results reveal that Learning Organization (Î²=0.289, p<0.05) and Knowledge Management (Î²=0.260, p<0.05) significantly enhance Competitive Advantage. Both Learning Organization (Î²=0.249, p<0.05) and Knowledge Management (Î²=0.523, p<0.05) positively influence Organizational Creativity, which subsequently strengthens Competitive Advantage (Î²=0.374, p<0.05). Organizational Creativity partially mediates the impact of Learning Organization (Î²=0.093, p<0.05) and Knowledge Management (Î²=0.196, p<0.05) on Competitive Advantage. The model shows that 50.9% of what affects creativity in organizations and 65.5% of what affects their competitive advantage can be understood from the data. This highlights how important creativity and knowledge are for staying competitive over time. Findings emphasize the strategic value for startups in integrating learning and knowledge frameworks to maintain competitive positioning. Findings emphasize the strategic value for startups in integrating learning and knowledge frameworks to maintain competitive positioning. These insights apply not just to startups but also to industries like manufacturing, healthcare, and education. By focusing on learning, managing knowledge well, and encouraging creativity, these sectors can boost innovation, work more efficiently, and become more adaptable. This will help them stay competitiveÂ overÂ time.